Renal and vascular effects of Crotalus durissus cumanensis venom and its crotoxin fraction - Pereira,TP (2011)
In this study, we evaluated the actions of Crotalus durissus cumanensis venom (CDCmV), and its crotoxin (Crtx) fraction, on renal and vascular functions in Wistar rats. In isolated perfused kidneys, CDCmV (10 µg/mL) significantly increased the perfusion pressure (PP) from 110.7 ± 2.4 to 125.3 ± 2.8 mmHg after 30 minutes. This effect was accompanied by an increased renal vascular resistance (RVR) from 5.4 ± 0.1 to 6.2 ± 0.2 mmHg/mL.g-1.min-1. We observed decreases in urinary flow (UF) from 0.13 ± 0.01 to 0.05 ± 001 mL.g-1.min-1 and glomerular filtration rate (GFR) from 0.66 ± 0.06 to 0.18 ± 0.02 mL.g-1.min-1. Crtx did not change PP or RVR, but diminished GFR (from 0.65 ± 0.05 to 0.26 ± 003 mL.g-1.min-1) and UF (from 0.11 ± 0.008 to 0.09 ± 0.008 mL.g-1.min-1). Both CDCmV and Crtx reduced the percentage of tubular transport of sodium, chloride and potassium. The cytotoxicity of these substances against MDCK cells was tested by the MTT method: only CDCmV caused a decrease in the cell viability with an IC50 of 5.4 µg/mL. In endothelium-intact isolated aortic rings, CDCmV (0.1 to 30 µg/mL) increased the sustained phenylephrine-induced contraction to a value of 130.0 ± 6.6% of its corresponding control, but showed a relaxant effect in endothelium-denuded preparations. Similar results were observed in aortic rings contracted with potassium (40 mM). Crtx was ineffective in aortic ring assays. Thus, it is reasonable to suggest that the renal effects induced by the CDCmV may be due to its influence on the endothelium's ability to release factors that can alter the contractile behavior of vascular smooth muscle. In conclusion, CDCmV is toxic to kidney cells. It changes parameters of the renal function including the glomerular filtration rate, renal vascular resistance and tubular transport. The actions induced by CDCmV also involve endothelium-dependent vasoactive properties. Their effects may be only partially attributed to Crtx.